Constitution on Ice - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper reports recent events in Iceland where the political agents of oligarchs didn t even bother to try to influence, let alone contest, a national referendum on a new constitution because, if they didn t like the result, they would simply find ways to nullify the outcome ex post. The paper reviews and explains the making of Iceland's crowd-sourced constitution bill from 2009 to 2014, and also offers an explanation as to why the bill failed to be passed by Parliament, addressing various criticisms leveled against the bill along the way. It needs to be emphasized that these criticisms, whether well founded or not (and they are not), are irrelevant because Parliament held a national referendum on 20 October 2012 in which the bill and its key individual provisions were accepted by an overwhelming majority of the voters. A democratic nation cannot under any circumstances permit the outcome of national elections, let alone a constitutional referendum, to be fixed ex post, but this is what the Icelandic Parliament is at present trying to do, flirting with a farewell to democracy.
Keywords: K10; 330; constitution; democracy; Iceland